(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Speed-limiting and stopping of the vehicle constitutes to loss of energy which was put in to reach the running speed. This loss in energy results in consumption of extra fuel. The wheels then generated mechanical energy is enough that it can be trapped into a battery after conversion. Thus, stored energy can be used to assist the HEV during running on fuel. The battery energy pushes and assists the HEV during takeoff and during gear changes. Fuzzy Logic plays a role in making and braking of electrical power transfer to the battery. Switching arrangement functions to switch the power train on the wheels from motors or the engine.